Factors influencing intention to implement urban agriculture among city dwellers - Ibrahim, Nur Dalinna (2017)
The economic transition from agricultural based to industrial based experienced by Malaysia has led to urbanization. Urbanization has put greater pressure on various resources such as residential availability, high cost of living, transportation, social amenities and food security. Those who live in urban areas have a limited source of food as food basically is produced in the rural areas and it is not enough to support the whole population. As agricultural territories have been converted to cities, housing area and infrastructural development, this scenario has caused insufficient domestic production to meet the rising demand for many agricultural produce. Thus Malaysia is now experiencing the negative balance of trade for the past decades as the country relies on imported food. With the high urbanization rate in Malaysia, it is a positive anticipation for Malaysian especially, the city dwellers to engage in urban agriculture. Moreover, urban agriculture may be lasting solution to the urgent need of addressing issues of urban food security, urban poverty as well as environmental protection. To drive the development of urban agriculture, there is a vital need to understand the acceptance of urban agriculture among the city dwellers. However at present, the information and study on urban agriculture in Malaysia is still limited since it is just developed. It very important to understand on city dwellers’ intention towards urban agriculture thus the suitable factor can be derive before embarking any program and campaign on implementing urban agriculture. In order to understand the factors that influence a city dweller’s intention towards implementing urban agriculture, this study have taken data from 1365 respondents. It is used to address the objective of the study. The factor analysis showed that perceived value, perceived behaviour control, facilitating condition, subjective norm, attitude and perceived risk were the factors influencing a city dweller’s intention towards urban aquaculture. More so, multiple regression analysis showed that knowledge, perceived usefulness and perceived value were important factors in developing an attitude to adopt the urban agriculture while facilitating condition remained the bedrock of determining perceived behavioural control. Attitude, perceived behavioural control and subjective norm also have a positive relationship with the intention to implement urban agriculture. Based on chi-square analysis, demographic profile such as age, gender, occupation, marital status and income have significant relationships with the intention to implement urban agriculture among the city dwellers. As conclusion, the study found out that interpersonal and external influences are significant to intention to adopt urban agriculture. It has also shown that respondents are reliance on their friends, family, colleagues or social media for information regarding urban agriculture. In other words, those who are important to them can influence their intention to adopt urban agriculture. It was also revealed that senior citizens who had retired and have high income showed more interest in urban agriculture than do the youngsters and unemployed person have low intention to adopt urban agriculture. With this result, it would lead the government agency and other parties to arranging suitable program on attracting city dwellers practicing urban agriculture. Besides that, exposure on the goodness of implementing urban agriculture and creating community garden surrounding the community area is one of method for city dwellers to perceive the goodness of adopting urban agriculture.